Operation mode of a step-feed anoxic/oxic process with distribution of carbon source from anaerobic zone on nutrient removal and microbial properties - Shen, Yijun; Yang, Dianhai; Wu, Yang; Zhang, Hao; Zhang, Xinxi (Scientific reports, 2019)
This study investigated the operation mode of a step-feed anoxic/oxic (A/O) process with distribution of the carbon source from the anaerobic zone in terms of the treatment effects on sewage with low carbon and high nitrogen and phosphorus. After seven phases of operation, an optimal flow distribution ratio of 75%:25% was obtained from the anaerobic zone, and the concentrations of chemical oxygen demand, ammonia nitrogen, total nitrogen, and total phosphorous in the effluent were 20.8, 0.64, 14.2, and 0.89 mg/L, respectively. The presence of an internal reflux system in the deaeration zone improved the treatment. 16S rRNA high-throughput sequencing revealed that the microbial communities in aerobic zone I(O1) of the first-step A/O sludge were different from those in aerobic zone I (O2) of the second-step A/O sludge, whereas microbial communities of the seed sludge were similar to those in O2 of the second-step A/O sludge. The richness and diversity of microbial communities in O1 of the first-step A/O sludge samples were higher than those in O2 of the second-step A/O and seed sludge. At the optimal flow distribution ratio, the microbial abundance and treatment removal efficiency were the highest.